Factors Associated With Short Length of Stay After Long Fusions for Adult Spinal Deformity: Initial Steps Toward Developing an Enhanced Recovery Pathway. Issue 6 (July 2021) - Lovecchio, Francis; Steinhaus, Michael; Elysee, Jonathan Charles; Huang, Alex; Ang, Bryan; Lafage, Renaud; Yang, Jingyan; Soffin, Ellen; Craig, Chad; Lafage, Virginie; Schwab, Frank; Kim, Han Jo
Study Design: Retrospective cohort study. Objectives: The identification of case types and institutional factors associated with reduced length of stay (LOS) is a key initial step to inform the creation of clinical care pathways that can assist hospitals to maximize the benefit of value-based payment models. The objective of this study was to identify preoperative, intraoperative, and postoperative factors associated with shorter than expected LOS after adult spinal deformity (ASD) surgery. Methods: A retrospective cohort study was performed of 82 patients with ASD who underwent ≥5 levels of fusion to the pelvis between 2013 and 2018. A LOS <6 days was determined as a basis for comparison, as 5.7 days was the "expected LOS" generated through Poisson regression modeling of the sample. Clinical, radiographic, surgical, and postoperative factors were compared between those staying ≥6 days (L group) and <6 days (S group). Logistic regression was used to identify factors associated with LOS <6 days. Results: A total of 35 patients were in group S (42.7%). Gender, age, body mass index, ASA (American Society of Anesthesiologists) class, and use of preoperative narcotics, revision surgery, day of admission, and surgical complications did not vary between the cohorts ( P > .05). Mild-moderate preoperative sagittal deformity (sagittal Schwab modifiers 0 or +), lower estimated blood loss (<1200 mL), fewer levels fused (7 vs 10 levels), shorter operating room time, procedure end time before 15:00, and no intensive care unit stay, were associated with short LOS ( P < .05). Only 1 major medical complication occurred in the short LOS group ( P < .05). Conclusions: This study identifies the ASD "case phenotype, " intra-, and postoperative benchmarks associated with shorter LOS, providing targets for pathways designed to reduce LOS.